A Hands-on Experiment of Caffeine Extraction from Tea Leaves Using Direct Sublimation: Learning Effectiveness for Secondary School Students - Horimatsu, Seika; Mizutani, Masanori; Miura, Hiroya; Ohkoshi, Emika (Journal of chemical education, 2025)
Hands-on experiments using everyday materials help students engage with learning and the world around them, increasing learning motivation. This is important for the field of chemistry, given learners’ declining interest in the subject and the association between chemistry and other sciences. Focusing on the direct sublimation of caffeine from tea leaves using a fast, affordable, and green extraction method, this study aimed to establish and optimize a hands-on experiment for secondary school students and evaluate students’ views of the program. A total of 119 secondary school students (13–15 years) received handouts explaining the procedure and providing explanations of theoretical and social aspects of the experiment and caffeine. The experiment took 60–70 min, after which students completed a questionnaire to indicate their interest in the task and provide feedback on the experience. Students rated the experiment positively with 98% very interested/interested in the study. The experimental phenomena were easily produced using a small quantity of reagent. Students observed the three states of matter and the process of matter changing through thermodynamics. Automated text analysis of the written responses indicated that students’ interest in the caffeine crystals was characterized by specific cognitive and affective components. “Exciting” and “fun” were frequently used keywords, suggesting that emotions are key to learning engagement. Students’ views may help educators better understand learner engagement with chemistry. The results have implications for chemistry educators, instructional designers, and policy makers, suggesting that practical activities using everyday items may lead to more effective and engaging chemistry teaching and learning.